Auditory middle latency response and phonological awareness in students with learning disabilities - Romero, Ana Carla Leite [UNESP]; Funayama, Carolina Araújo Rodrigues; Capellini, Simone Aparecida [UNESP]; Frizzo, Ana Claudia Figueiredo [UNESP] (International Archives Of Otorhinolaryngology, 2015)
Introduction Behavioral tests of auditory processing have been applied in schools and highlight the association between phonological awareness abilities and auditory processing, confirming that low performance on phonological awareness tests may be due to low performance on auditory processing tests. Objective To characterize the auditory middle latency response and the phonological awareness tests and to investigate correlations between responses in a group of children with learning disorders. Methods The study included 25 students with learning disabilities. Phonological awareness and auditory middle latency response were tested with electrodes placed on the left and right hemispheres. The correlation between the measurements was performed using the Spearman rank correlation coefficient. Results There is some correlation between the tests, especially between the Pa component and syllabic awareness, where moderate negative correlation is observed. Conclusion In this study, when phonological awareness subtests were performed, specifically phonemic awareness, the students showed a low score for the age group, although for the objective examination, prolonged Pa latency in the contralateral via was observed. Negative weak to moderate correlation for Pa wave latency was observed, as was positive weak correlation for Na-Pa amplitude.
Keywords: Cognition; Evoked potentials auditory; Hearing; Learning; Learning disability